Diagnostic Value of Ureteric Jet Frequency Examination using Color Doppler Ultrasonography to Predict Success of Retrograde DJ Stent Insertion in Uterine Cervicis Carcinoma patients with Hydronephrosis - sriyono, sriyono; Santoso, Adi; Djojodimedjo, Tarmono; Soebadi, Moh Ayodhia; Pudjirahardjo, Widodo J (Indonesian Journal of Urology, 2015)
AbstractObjective:  To prove that ureteric jet examination using Color Doppler Ultrasonography (CDU) can be used as a diagnostic tool to predict success of retrograde Double J Stent insertion in uterine cervicis carcinoma patients with hydronephrosis.Materials and Methods: This observational analytic study took 32 samples since May until October 2013. Before, the ureteric jet were counted for 5 minutes using CDU, then continued on the same day with cystoscopy and retrograde DJ Stent insertion. The analysis was using Chi-Square and also Coefficient Contingency test.Results: In both Chi-Square and Coefficient Contingency test, it is proven a significant correlation between success of retrograde DJ Stent insertion and Blood Urea Nitrogen (BUN), creatinine value, grade of hydronephrosis and also ureteric jet examination using CDU, with probability value (p < 0,005). The normal of BUN, creatinine level and the lower grading of hydronephrosis, the more likely successful DJ Stent insertion. Successfulness of DJ Stent insertion is also greater in a positive ureteric jet samples on examination using CDU, with sensitivity value 90,9% and specificity 89,5%, positive predictor value 83,3%, negative predictor value 95% and accuracy value 0,9.Conclusion: Ureteric jet frequency examination using CDU can be used as a success predictor of retrograde DJ Stent insertion in hydronephrosis uterine cervicis carcinoma patients with sensitivity value 90,9% and specificity 89,5%.Keywords: Ureteric jet, Color Doppler Ultrasonography, Double J Stent, Uterine Cervicis Carcinoma